Is venture capital a regional business? The role of syndication - Michael Fritsch; Dirk Schilder (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
We investigate whether the supply of Venture Capital (VC) in Germany is driven by spatial influences. The study is based on information from more than 300 VC investments made in Germany in the year 2004 and 2005. We find evidence that the geographical distance between a VC company and the portfolio firm is not an important factor for German VC investments. Syndication of investments helps to overcome the problem of distance to portfolio firms if one of the investors is located close to the investment. Altogether, we find no evidence for a severe regional equity gap for young and innovative companies in Germany.
Keywords: G24; O16; D21; M13; R12; 330; Venture Capital; regional equity gap; start-up financing; entrepreneurship